Spiritualitas dan Formasi Karakter Kristen - Martina Labora Nainggolan; Yusniarti Situmorang; Rahel Dwi Ivana; Baginda Sitompul (Lembaga Pengembangan Kinerja Dosen, 2026)
Christian Religious Education plays an important role in shaping individuals who possess not only intellectual knowledge but also a healthy spiritual life and godly character. In the midst of rapid technological advancement, globalization, and moral value shifts, the development of Christian spirituality and character formation has become increasingly essential. Christian spirituality refers to a personal and living relationship with God through Jesus Christ, while Christian character formation is the process of developing attitudes, values, and behaviors that reflect the character of Christ in daily life. This paper aims to examine the concepts of Christian spirituality and character formation through discussions on Christian character education, the spirituality of teachers and students, Christian ethics in education, integrity formation, and spiritual disciplines. The study employs a library research method by collecting and analyzing relevant sources, including the Bible, books, journals, and other academic references. The findings reveal that Christian spirituality and character are closely interconnected and cannot be separated. Christian character education, which is grounded in the Word of God, helps develop individuals who demonstrate love, honesty, humility, responsibility, and integrity. Furthermore, the spirituality of teachers and students serves as the foundation of the educational process, while Christian ethics, integrity, and spiritual disciplines play significant roles in shaping lives that are pleasing to God. Therefore, the consistent application of Christian spirituality and character formation can produce individuals who are spiritually mature, possess noble character, and are capable of being witnesses of Christ in society.